A study of Indonesian Muslim consumer's purchase intention towards sustainable fashion - Kusmarsetyo, Hana Kamila (Kulliyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
Sustainable fashion is one of the alternatives that may overcome the environmental issues caused by fashion industry, especially fast fashion. Sustainable fashion is believed to be able to protect ethical working conditions as well as the natural resources from dangers of waste. The number of Muslim wear demand in Indonesia and awareness of sustainability are seen to continue to increase every year. This study examined the factors that influenced Indonesian Muslim consumer’s purchase intention towards sustainable fashion. Quantitative method is used in this research and a specifically chosen primary data are used to get the results of the study. A total of 208 respondents were gathered and SPSS is used to analyse the data. Based on the data, the findings indicated that only perceived behavioral control have a significant positive relationship with purchase intention towards sustainable fashion while other purchase intention factors tested in this study have no significant positive relationships with purchase intention towards sustainable fashion.